Involved fathering and men's adult development : provisional balances - Palkovitz, Robin Joseph, 1954- (Lawrence Erlbaum Associates, 2002)
A study of involved fathering and men's adult development. It is an interdisciplinary work that synthesizes theoretical, empirical and anecdotal writings from different fields along with the author's analysis of extensive interviews with fathers.